Desenvolvimento e aplicações da técnica espectroscopia Raman anti-stokes coerente multiplex - Lady Katherine Soto Gómez (2018)
Different techniques of optical microscopy such as fluorescence, Raman spectroscopy and nonlinear optical have been used to study biological systems and also to diagnose diseases. For example, conventional Raman spectroscopy can generate images of different proteins using the characteristic vibration modes of this protein as a marker. However, due to the low efficiency of the Raman process in biological samples, techniques such as CARS (Coherent Anti-Stokes Raman Spectroscopy) have been used to obtain images of fluorescent labels and in real time using molecular vibrations as label. These images allows the study of organ functioning in vivo, which makes it a very useful tool for studies applied to biology. In this dissertation we deal with linear and non-linear optical effects, especially the theories of conventional Raman and experimental setup, CARS and multiplex CARS techniques. CARS and Multiplex CARS are stimulated Raman techniques, being a case of four wave mixing (FWM). In this process, two pump beams and one Stokes beam are combined to generate another CARS beam, where the energy of these input beams is selected so that the difference between them is the vibration modes of a particular sample. We implemented two types of experimental multiplex CARS experimental setup in this dissertation. We compared the two experimental assemblies using reference samples (acetonitrile, methanol and acetone) and chose the system that best suits our needs for the mapping of samples of polystyrene and biological tissue. With the developments made in this dissertation, we can study problems related to biology, such as the detection of beta-amyloid protein plaques related to Alzheimer's disease.